Therapeutic role of calcium and vitamin K3 in chemically induced hepatocarcinogenesis – new tools for cancer treatment. (27th May 2019) - Anwar, Firoz; Khan, Ruqaiyah; Sachan, Richa; Kazmi, Imran; Rawat, Alisha; Sabih, Abdullah; Singh, Rajbala; Afzal, Muhammad; Ahmad, Aftab; Al-Orab, Abdulaziz S.; Al-Abbasi, F. A.; Bhatt, Prakash Chandra; et al.
Abstract: HCC has been reported to be immensely occurring carcinoma worldwide. Recent days the mortality occurred due to liver cancer has also been found to be increased at an alarming speed affecting mostly the young patients. The aim of the current study was to decipher the role of calcium and vitamin K3 in the treatment of chemically induced hepatocarcinogenesis in the male Wistar rats. Liver cancer was induced via a subnecrogenic dose of 160 mg/kg body weight, diethylnitrosamine (DENA) when associated with fasting/refeeding in male Wistar rats. It elevated the serum glutamate oxaloacetate (SGOT), serum glutamate pyruvate transaminase (SGPT), alkaline phosphatase (ALP), bilirubin, total cholesterol (CH), triglycerides (TG), alfa-fetoprotein (AFP) and reduced high-density lipoprotein (HDL). Histopathological examination of liver tissue showed marked carcinogenicity of the chemical carcinogen. Food, water intake and animal weights were also assessed, respectively. The animals exposed to DENA showed a significant decrease in the body weight. The elevated levels of serum SGOT, SGPT, ALP, AFP, TC and TG were restored by administration of calcium and Vit K ( ad libitum ) combination at higher dose than the normal dietary requirement (3 mg/kg) daily for 12 weeks p.o. Physiological and biochemical analysis showed the beneficial effects of calcium and vitamin K3 combination in the animals exposed to DENA. The results deciphered the beneficial effects of calcium and vitamin K3 in combination.